COMPATIBILITY OF FOUR TROPICAL WOOD SPECIES AND SAGO STEM TO CEMENT AND PROPERTIES OF MANGIUM CEMENT BONDED PARTICLEBOARD - Dede Hermawan1; Ismail Budiman; Herman Siruru; Jessica Hendrik; Gustan Pari (BRIN Publishing, 2020)
The quality of the cement board depends on the compatibility between cement and particles fromlignocellulosic biomass. The purpose of this study was to determine the compatibility between cementand particles from four tropical wood namely mangium (Acacia mangium Willd), teak (Tectona grandisLinn. F.), gelam (Melaleuca leucadendron (L.), dadap (Erythrina variegata L.), and sago stem (Metroxylonsago Rottb.), and to determine the physical and mechanical properties of the mangium cement boardproduced by adding magnesium chloride (MgCl2) as an accelerator. This research was conducted intwo steps. The first step consisted of measuring the hydration temperature of a mixture of cement with particles from the four wood species and sago stems by adding magnesium chloride (MgCl2),with variations of 0%, 2.5%, 5%, and 7.5% based on the cement weight. Two types of mixturesfrom the first step were then used in the second step, namely the manufacture of cement board. The cement board was made using a weight ratio of mangium particles:cement:water of 1:2.7:1.35. Theboard is made with a target density of 1.2 g/cm3. Physical and mechanical testing refers to the ISO8335-1987 standard. The results of the hydration temperature showed that all of the mixtures wereclassified into “low inhibition”, except for mixture between cement and mangium particles without a catalyst which was included in the classification of “moderate inhibition”. While the results of cement board tests indicate that the cement boards made from mangium wood particles with 5%MgCl2addition had better properties compared to mangium cement boards without catalysts.